Managing labour migration in Europe : Ideas, knowledge and policy change - Balch, Alex (Book collections on Project MUSE., 2010)
Labour migration has become one of the hot topics in Europe, especially since 2000 with the shift from restriction to managed migration. This book provides an authoritative account of policy change over labour migration in Europe during this new era of governance.